The perspectives of augmentative and alternative communication experts on the clinical integration of non-invasive brain-computer interfaces. Issue 4 (2nd October 2022) - Pitt, Kevin M.; McKelvey, Miechelle; Weissling, Kristy
ABSTRACT: As brain-computer interface for augmentative and alternative communication access (BCI-AAC) development continues to consider avenues for translation into the clinical setting, the perspectives of clinican experts in AAC should be considered. Therefore, 11 USA-based speech-language pathologists who are experts in AAC completed a semistructured interview along with Likert scale measures to assess their perspectives on BCI-AAC. The interviews and scales explored the potential impact of BCI-AAC, along with barriers and solutions to BCI-AAC implementation. Speech-language pathologists estimated that 1.5% to 50% of their caseload may benefit from BCI-AAC across various settings. Further, identified barriers and solutions included (a) BCI-AAC implementation and support, (b) funding and access, (c) applicability and literacy skills, (d) assessment and training in supporting outcomes, and (e) motivation and customization. Results reinforce and extend existing directions for BCI-AAC translation such as user-centered assessment, stakeholder support, and populations who may benefit from intervention, such as children.